In vivo Efficacy of Ethanolic Extract of Cassia nigricans (Vahl) Against Gastro-Intestinal Nematodes (GIN) of Goats in West Nile Region, Uganda - Oba, Peter; Asizua, Denis; Komuntaro, Godwin; Kasozi, Nasser; Kalenzi, Moses; Apamaku, Michael; Kateregga, John; Okwee-Acai, James; Ndukui, Jimmy G.; Kabasa, William; Benda, Katali K. (Am J Clin Exp Med, 2016)
Several plants are used by farmers for the treatment of gastrointestinal nematodes (GIN) in goats. However, their phytochemical properties, efficacy and safety is largely unknown. A trial was therefore designed to determine in vivo efficacy of ethanolic extract of Cassia nigricans against gastrointestinal nematodes (GIN) in goats. Cassia nigricans leaves were collected from Arua District, Uganda. Ethanolic extraction method was to prepare extracts and the experimental goats were dosed accordingly. Treatments were assigned to five (5) groups of goats (n=9) as follows: Group A, the negative control (30ml of distilled water; group B, the positive control (Albendazole 10%, 8mg/kg). Groups C, D and E received extracts at 50, 100 and 150mg/kg, respectively. Live weights (LWs kg), faecal samples (for faecal egg count reduction (FECR) based on eggs per gram (EPGs) of faeces, packed cell volume (PCV %), total protein (TP g/dL), body condition scores (1-5) and Faffa Malan Chart (FAMACHA scores 1-5) were taken on day 1 of the experiment and subsequently at 7-day intervals for 4 weeks. Results revealed that a significant increase in LWs by 2nd week was observed in goats treated with Albendazole from 20.8 ± 1.9 to 21.9 ± 1.8 (p ≤ 0.05). No change in LWs and in TP was observed in all other groups (p ≥ 0.05). Only Albendazole treated group exhibited a significant increase of PCV in the 2nd week (p ≤ 0.05). EPGs were observed to significantly drop in those treated with Albendazole by the 2nd week from 300 ± 91 to 0 ± 0 and extract at 150 mg/kg dose from 740 ± 236 to 60 ± 25 (p ≤ 0.05). The FECR for Albendazole, 50, 100 and 150 mg/kg doses of the extract were found to be 100%, 37.3%, 66.6% and 83.8% respectively. Only at 150 mg/kg dose did the extract show moderate efficacy in reducing mixed Strongyle spp faecal egg counts in goats. Strongyles spp. were the most predominant genera of nematodes found in goats. Further evaluations of leaf extracts and other plant parts is necessary to establish its potential as a source of local effective remedy against gastro-intestinal nematodes in goats.
Keywords: Ethnoveterinary; Medicine; Cassia nigricans; Gastro-Intestinal; Nematodes